2004
DOI: 10.1128/iai.72.11.6492-6502.2004
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to the N-Terminal Block 2 ofPlasmodium falciparumMerozoite Surface Protein 1 Are Associated with Protection against Clinical Malaria

Abstract: This longitudinal prospective study shows that antibodies to the N-terminal block 2 region of the Plasmodium falciparum merozoite surface protein 1 (MSP-1) are associated with protection against clinical malaria in an area of stable but seasonal malaria transmission of Ghana. Antibodies to the block 2 region of MSP-1 were measured in a cohort of 280 children before the beginning of the major malaria transmission season. The cohort was then actively monitored for malaria, clinically and parasitologically, over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
97
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 42 publications
(58 reference statements)
10
97
1
5
Order By: Relevance
“…Antibodies against MSP1-19 were also predominantly of the IgG1 and IgG3 isotypes, in agreement with the results of previous studies from countries in Africa where malaria is endemic (14,22). In some studies, scientists have found that high levels of anti-MSP1 IgG1 antibodies are associated with protection against malaria attacks (22), whereas in other studies, the scientists failed to observe such an association (19).…”
Section: Discussionsupporting
confidence: 79%
“…Antibodies against MSP1-19 were also predominantly of the IgG1 and IgG3 isotypes, in agreement with the results of previous studies from countries in Africa where malaria is endemic (14,22). In some studies, scientists have found that high levels of anti-MSP1 IgG1 antibodies are associated with protection against malaria attacks (22), whereas in other studies, the scientists failed to observe such an association (19).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, early studies have demonstrated the presence of naturally acquired antibodies against the N terminus (7, 9) and C terminus (13,28,31) of PfMSP1. The presence of such naturally acquired antibodies against MSP1 was later correlated to clinical protection in some, though not all, studies (8,10,12,14,24,25,26). Although the role of other portions of this large molecule remains mostly unknown, these studies have validated the N and C termini of PfMSP1 as solid subunit vaccine candidates against P. falciparum.…”
mentioning
confidence: 86%
“…personally diagnosed these patients, and after obtaining ethical consent to not treat them with drugs, actively followed them up twice a week for 2 months to guarantee that they did not develop malaria symptoms. Moreover, we analyzed independently the N and C termini of PvMSP1, as antibodies against both regions of the MSP1 of P. falciparum have been associated with clinical protection and acquired immunity (8,10,12,14,24,25,26). Strikingly, in spite of being the most immunogenic portion of PvMSP1 in natural infections and being capable of boosting (34), there was no association of antibody responses against the C terminus of PvMSP1 in survey A with clinical protection or risk of P. vivax infection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies which bind Fc receptors and mediate antibody-dependent cytotoxicity, growth inhibition, or phagocytosis (so-called "cytophilic" antibodies) have repeatedly been shown to be highly effective at clearing blood stage malaria parasites, both in humans (14,43) and in mice (36,38,55). In humans, immunoglobulin G3 (IgG3) is especially valuable in this regard (4,19), and the presence of IgG3 to various merozoite-associated antigens has been linked to protective immunity in seroepidemiological studies (10,15,35,51,56).…”
mentioning
confidence: 99%